Muscle injuries in sports - Müller-Wohlfahrt, Hans-Wilhelm, 1942-; Ueblacker, Peter; Haensel, Lutz; Garrett, William E.; Dvořák, J. (Jirí), 1948- (Thieme, 2013)
The average professional athlete sustains approximately two injuries per year. Not only do these injuries incur primary treatment costs, but significant secondary costs also arise due to lost productivity and absence from work. The most common sports-related injuries involve the muscles. Injuries of the skeletal muscles are often underestimated, misinterpreted, and improperly treated. Lack of training and continuing education in this area, a lack of research, the so far absence of a practical, comprehensive, universal classification system for muscle injuries and even a lack of uniform terminology. The editors of this book, as well as the contributing authors have had decades of practical experience in caring for thousands of professional and amateur athletes.